Correlation between Chemical Dopants and Topological Defects in Catalytically Active Nanoporous Graphene. Issue 48 (10th October 2016) - Ito, Yoshikazu; Shen, Yuhao; Hojo, Daisuke; Itagaki, Yoji; Fujita, Takeshi; Chen, Linghan; Aida, Tsutomu; Tang, Zheng; Adschiri, Tadafumi; Chen, Mingwei
Abstract : The interplay between chemical dopants and topological defects plays a crucial role in electrocatalysis of doped graphene. By systematically tuning the curvatures, thereby the density of topological defects, of 3D nanoporous graphene, the intrinsic correlation of topological defects with chemical doping contents and dopant configurations is revealed, shining lights into the structural and chemical origins of HER activities of graphene.